Draft Annual Plan 1998-99 Government of Mizoram - Planning Commission (Planning Commission, 1998)
The size of Mizoram Annual Plan has been fixed at Rs. 333.00 crores in the meeting between the Deputy Chairman, Planning Commission and the Chief Minister of Mizoram on 9.10.1998 and sectoral allocation has been decided subsequently by Govt, of Mizoram. Preparation of draft Annual Plan 1998-99 was delayed due to late receipt of the summary records of the discussion held on 9.10,1998. For the 9th Five Year Plan 1997-2002, Rs. 1618.51 crores have been allotted to Mizoram. In the first year of 9th Plan i.e. 1997-98, Rs. 290.00 crores have been approved by Planning Commission. the Govt, of Mizoram is grateful to the Planning Commission for granting substantial increase in the Annual Plan allocation.
Government of Mizoram Planning and Programme Implementation Department